Profile of Student Misconceptions on Static Fluids: A Meta-Analysis Study - Ahmad Busyairi; Muhammad Zuhdi (Universitas Hamzanwadi, 2024)
Misconceptions in physics learning, especially regarding static fluids, are one of the main challenges in learning which can hinder students' understanding of basic concepts and the development of high-level thinking skills. This research aims to identify and analyze misconceptions that occur among students regarding static fluid material. This research is a meta-analysis study. This research examines the results of previous research that discusses misconceptions on the topic of static fluids with a focus on the types of misconceptions that often arise and the factors that influence them. The data analyzed were obtained from a number of studies involving various methods, such as diagnostic tests, interviews, and experimental research. The meta-analysis results show that the most common misconceptions occur in the understanding of hydrostatic pressure, Archimedes' principle, and Pascal's law, where students often associate these concepts with inaccurate everyday intuitions. Apart from that, factors such as less contextual teaching, limited learning experience, and difficulties in visualizing abstract concepts are the main causes of misconceptions. This research suggests the importance of a more explicit and concept-based teaching approach, as well as the use of visual aids or simulations to help students build a more precise understanding of static fluids.